THE INFLUENCE OF THE APPLICATION OF THE THINK PAIR SHARE (TPS) COOPERATIVE LEARNING MODEL ON STUDENTS' REASONING ABILITY AND MATHEMATICAL ABSTRACT ABILITY : PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF THINK PAIR SHARE (TPS) TERHADAP KEMAMPUAN PENALARAN SISWA DAN KEMAMPUAN ABSTRAK MATEMATIS - Ahmad Farham Majid; Muhammad Mursyid Munir; Mardhiah; Fitriani Nur; A. Sriyanti (MaPan : Jurnal Matematika dan Pembelajaran, 2022)
This study aims to determine how the effect applying the think pair share learning method has on the reasoning and mathematical abstraction abilities of class X students of SMA Negeri 9 Makassar. This study used a quantitative approach with the type of experimental research using a quasi-experimental research design with a non-equivalent control group design. The population in this study were all 290 class X students of SMAN 9 Makassar. The sample in this research was an experimental class of 36 people and a control class of 36 people. The instrument in this study was a test to measure reasoning abilities and mathematical abstraction in the form of a pretest and posttest. The data analysis technique used is descriptive statistical analysis and inferential statistical analysis, namely the multivariate analysis of variance (manova) test. The results of this study indicate that: (1) The average results of students' mathematical reasoning abilities in the experimental class and the control class increased. (2) The average results of students' mathematical abstraction abilities in the experimental class and the control class increased. (3) There is an influence of the TPS type cooperative learning model's application on the reasoning and mathematical abstraction abilities of SMA Negeri 9 Makassar class X students. (4) There is an effect of applying the TPS type cooperative learning model to the mathematical reasoning abilities of SMA Negeri 9 Makassar class X students. (5) There is an effect of applying the TPS type cooperative learning model to the mathematical abstraction abilities of SMA Negeri 9 Makassar class X students.